Nurse educators’ perspectives in facilitating ethics education: a descriptive qualitative study - Zolkefli, Yusrita; Muharram, Siti Hanna; Nursalam, Nursalam; Atan, Ashikin (Elsevier, 2024)
Background Developing a professional nurse with ethical competence requires an efficient teaching and learning process.